The Effectiveness Of Problem Based Learning In Improving Arabic Reading Skills - Ahmad Fikri; Noza Aflisia; Harisah Harisah (Ijaz Arabi Journal of Arabic Learning, 2023)
The Problem Based Learning method relates learning material to real-world situations to help students understand Arabic material better. A quantitative study with an experimental approach was conducted to determine the effectiveness of using the PBL method in Arabic reading proficiency classes. The one group pretest posttest design was used in this study. The results of the study show that in general, the use of PBL in Research Methodology learning is effective both in terms of the learning process and learning outcomes. However, the research findings show that the use of PBL in learning the Arabic Language Research Methodology Course is less effective for students who have low competency levels, poor learning attitudes, lack of willingness to learn, low learning discipline, and are less active in classroom.